2014
DOI: 10.1161/circresaha.115.304388
|View full text |Cite
|
Sign up to set email alerts
|

Small Heterodimer Partner Blocks Cardiac Hypertrophy by Interfering With GATA6 Signaling

Abstract: Cardiac hypertrophy is an increase in the individual cellular volume of the heart and is an adaptive response to exogenous stresses. The increase in cellular volume is associated with reactivation of the fetal gene program, which is finely regulated by diverse cardiac transcription factors.1 Specifically, GATA4, GATA6, myocyte enhancer factor 2C, nuclear factor of activated T cells, NK2 homeobox 5, and serum response factor have been shown to be involved in the development of cardiac hypertrophy.1 GATA4 and GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Recently, roles for FXR in myocardial injury and SHP in cardiac hypertrophy have been identified. Hence, we examined whether deletion of Fxr or Shp alone led to the altered metabolic gene expression profile in DKO mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, roles for FXR in myocardial injury and SHP in cardiac hypertrophy have been identified. Hence, we examined whether deletion of Fxr or Shp alone led to the altered metabolic gene expression profile in DKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, deletion of SHP causes hypertrophy and bradycardia, along with a few changes in the metabolic gene expression pattern compared to DKO mice (http://onlinelibrary.wiley.com/doi/10.1002/hep.28890/suppinfo). Our data validate the recently described role for SHP in regulating cardiac growth . It was shown that SHP is a novel antihypertrophic regulator that acts by interfering with GATA6 signaling in the heart .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these signaling cascades likely regulate GATA6 PTMs, as of yet, none have been specifically associated with cardiac adaptive stress response, although S290 phosphorylation by AKT2 and direct interaction with the HAT P300 have been reported in VSMCs . GATA6 interacting proteins in the adaptive stress response include small heterodimer partner (a GATA6 repressor), and interestingly, GATA4 (Table ) . Although the role of these heterotypic GATA interactions in cardiac hypertrophy have not been elucidated, GATA6 and 4 synergize to transactivate natriuretic factors genes whose upregulation is a hallmark of cardiac hypertrophy …”
Section: Roles Of Gata Factors In Adult Heart Health and Diseasementioning
confidence: 99%
“…78,79 GATA6 interacting proteins in the adaptive stress response include small heterodimer partner (a GATA6 repressor), and interestingly, GATA4 (Table 4). 44,77,80 Although the role of these heterotypic GATA interactions in cardiac hypertrophy have not been elucidated, GATA6 and 4 synergize to transactivate natriuretic factors genes whose upregulation is a hallmark of cardiac hypertrophy. 44,77 The findings regarding GATA6 and 4 in hypertrophy are especially notable because of their apparent overlap in function.…”
Section: Gata6mentioning
confidence: 99%